Pelatihan Penulisan Artikel Ilmiah Untuk Peningkatan Profesionalisme Guru SMA Negeri 1 Pamboang - Indah Panca Pujiastuti; Ariandi Ariandi; Nurmuliayanti Nurmuliayanti; Hasbahuddin Hasbahuddin (STKIP Andi Matappa, 2023)
Increasing scientific publications is an indicator that shows the teacher's ability to write down his thoughts and disseminate scientific activities that have been carried out. Currently, the average SMA Negeri 1 Pamboang Majene has never participated in scientific article writing training activities, so partners need scientific article training to increase teacher professionalism, especially at State High School. 1 Pamboang Majene. The PKMM team collaborated with SMA Negeri 1 Pamboang Majene to conduct training and mentoring for SMA Negeri 1 Pamboang teachers. This activity was carried out in October 2022-January 2023. This activity was attended by 29 participants from SMA Negeri 1 Pamboang Majene offline. The title of the workshop activity was themed